Management of sleep‐time masticatory muscle activity using stabilisation splints affects psychological stress. (7th November 2013) - Takahashi, H.; Masaki, C.; Makino, M.; Yoshida, M.; Mukaibo, T.; Kondo, Y.; Nakamoto, T.; Hosokawa, R.
Summary To treat sleep bruxism (SB), symptomatic therapy using stabilisation splints (SS) is frequently used. However, their effects on psychological stress and sleep quality have not yet been examined fully. The objective of this study was to clarify the effects of SS use on psychological stress and sleep quality. The subjects (11 men, 12 women) were healthy volunteers. A crossover design was used. Sleep measurements were performed for three consecutive days or longer without (baseline) or with an SS or palatal splint (PS), and data for the final day were evaluated. We measured masseter muscle activity during sleep using portable electromyography to evaluate SB. Furthermore, to compare psychological stress before and after sleep, assessments were made based on STAI‐JYZ and the measurement of salivary chromogranin A. To compare each parameter among the three groups (baseline, SS and PS), Friedman's and Dunn's tests were used. From the results of the baseline measurements, eight subjects were identified as high group and 15 as low group. Among the high group, a marked decrease in the number of bruxism events per hour and an increase in the difference in the total STAI Y‐1 scores were observed in the SS group compared with those at baseline (P < 0·05). No significant difference was observed in sleep stages. SS use may be effective in reducing the number of SB events, while it may increase psychological stress levels, and SS use did not apparently influence sleep stages.